(untitled) (Archives of Mechanics - Test, 1999)
The present work extends Chandrasekhar’s theory CHANDRASEKHAR [2] of axisymmetric capillary instability of a hollow jet. Here the instability of this model is investigated for all (non)-axisymmetric perturbation modes under the combined effect of the capillary and electrification forces. The electrification dispersion relation has been derived, studied analytically and numerically, and the (un-) stable domains are identified. Some reported results are recovered as limiting cases. The principle of the exchange of instability is valid. The capillary instability of a hollow jet becomes worse in the presence of the electrification forces.